Early lenalidomide treatment for low and intermediate‐1 International Prognostic Scoring System risk myelodysplastic syndromes with del(5q) before transfusion dependence. (17th September 2015) - Oliva, Esther N.; Lauseker, Michael; Aloe Spiriti, Maria Antonietta; Poloni, Antonella; Cortelezzi, Agostino; Palumbo, Giuseppe A.; Balleari, Enrico; Sanpaolo, Grazia; Volpe, Antonio; Ricco, Alessandra; Ronco, Francesca; Alati, Caterina; et al.
Abstract: Lenalidomide is approved for the treatment of transfusion‐dependent (TD) del(5q) myelodysplastic syndromes (MDS). However, few data are available in patients with transfusion‐independent (TI) del(5q) MDS. In the first, observational, part of this 2‐part study, we assessed the impact of transfusion dependence on overall survival (OS) and non‐leukemic death in untreated del(5q) MDS patients who were TD ( n = 136), TI with hemoglobin (Hb) ≥10 mg/dL ( n = 88), or TI with Hb <10 mg/dL ( n = 96). In the second, interventional, part we assessed the quality‐of‐life (QoL) benefits and clinical efficacy of lenalidomide (10 mg/day) in 12 patients with TI del(5q) MDS and Hb <10 mg/dL. In the untreated population, OS was significantly longer in TI than in TD patients (TI [Hb ≥10 g/dL], 108 months; TI [Hb <10 g/dL], 77 months; TD, 44 months). Transfusion dependence also negatively impacted non‐leukemic death rates. In the interventional part of the study, baseline Hb levels were found to correlate significantly with physical ( R = 0.666, P = 0.035) and fatigue ( R = 0.604, P = 0.049) QoL scores. Median physical QoL scores improved significantly after 12 weeks' treatment with lenalidomide (+12.5; P = 0.020). Evaluable TI patients experienced early increases in Hb levels, and all attained an erythroid response. Our findings suggest that TI patients with moderate anemia may benefit from early treatment with lenalidomide. Abstract : In this 2‐part study, transfusion dependence was found to negatively impact both overall survival and the risk of non‐leukemic death in untreated patients with low or intermediate‐1 (Int‐1) International Prognostic Scoring System (IPSS) del(5q) myelodysplastic syndromes. Lenalidomide treatment was associated with clinical efficacy and quality‐of‐life benefits in low and Int‐1 IPSS risk del(5q) patients who had not yet progressed to transfusion dependence.